OPTIMIZATION OF CELLULASE PRODUCTION BY CANDIDA G3.2 FROM THE RHIZOSPHERE OF GUNUNG ANYAR MANGROVE SURABAYA - Alami, N. H.; Kuswytasari, N. D.; Zulaika, E.; Shovitri, M. (Proceedings of the International Conference on Green Technology, 2017)
Microbial cellulases are the enzymes widely used in many biochemical industries. Yeast has potential to degrade cellulose because of cellulase activity. Yeast from the genus of Candida G3.2 has the ability to hydrolaze cellulose which tested by cellulolytic index. The purpose of this study is to determine the incubation time and the combination of physicochemical factors (pH and temperature) optimal for the production of cellulase enzymes by yeasts.The study design by factorial which analyzed by descriptive quantitative. This study begins with the optimization of cellulase production, starting with the optimization of the incubation period and followed by a combination of temperature optimization (room, 45°C, 55°C) and pH (4.5, 6, 8) then measure the cellulase activity. The results showed that the best incubation period for cellulase production is 72 hours (267 U/ml) with a combination of temperature 55°C and pH 6 (369.8 U/ml).